2007
DOI: 10.1108/02686900710829417
|View full text |Cite
|
Sign up to set email alerts
|

Perceived environmental uncertainty, supply chain purchasing strategy, and use of MAS information

Abstract: PurposeThe purpose of this paper is to investigate the relationship between perceived environmental uncertainty (PEU), supplier development (SUD) and the use of broad scope management accounting systems (MAS) information. In recent years, many companies have come to recognize the important role supply chain purchasing strategy plays in achieving competitive advantage. One of the key components of the supply chain purchasing strategy is supplier development. In addition, there have been calls for research into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
3
22
0
2
Order By: Relevance
“…MO and use of MASs accounting in a market-oriented setting (Agbejule, 2005;Agbejule and Burrowes, 2007;Mia and Winata, 2014). Second, the findings from this study support the RBV (Chenhall, 2003) and the knowledge-based view (Grant, 1996) while arguing and providing evidence that MAS is a resource that meets the VRIN conditions and can enable firms to promote learning and create knowledge for competitive advantage and superior firm performance in a competitive environment.…”
supporting
confidence: 58%
“…MO and use of MASs accounting in a market-oriented setting (Agbejule, 2005;Agbejule and Burrowes, 2007;Mia and Winata, 2014). Second, the findings from this study support the RBV (Chenhall, 2003) and the knowledge-based view (Grant, 1996) while arguing and providing evidence that MAS is a resource that meets the VRIN conditions and can enable firms to promote learning and create knowledge for competitive advantage and superior firm performance in a competitive environment.…”
supporting
confidence: 58%
“…Recent research investigated the relationship between PEU, supplier development and the use of broad scope management accounting system information. The findings indicated that the increase in PEU motivates firms to adopt more supply chain strategies, which place more demands on the use of management accounting system (Agbejule & Burrowes, 2007). These research findings lead to the conclusion that PEU is a potential contextual variable in a contingency model.…”
Section: Exogenous Factor: Perceived Environmental Uncertainty (Peu)mentioning
confidence: 70%
“…Gul and Chia (1994) found a statistically significant three-way interaction between a manager's perceptions of environmental uncertainty, decentralized organizational structure, and MAS information used on managerial performance. Furthermore, Agbejule and Burrowes (2007) reported that when managers perceived their environment to be uncertain they flexed their supply chain purchasing strategies by making extensive use of MAS information, which resulted in an overall improvement in performance. The results obtained in this research support the findings of Gul and Chia (1994) and Agbejule and Burrowes (2007), and further emphasize the GMs' transformational leadership style and DMs application of MAS information in the hotel industry, particularly to help overcome the competitive environment and the unique characteristics of hotel products and services.…”
Section: Discussionmentioning
confidence: 98%
“…These two elements can create stress and ambiguity for DMs. According to Agbejule and Burrowes (2007) and Gul and Chia (1994), to effectively drive the performance, managers need to first find and then process appropriate MAS information. Gul and Chia (1994) found a statistically significant three-way interaction between a manager's perceptions of environmental uncertainty, decentralized organizational structure, and MAS information used on managerial performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation